Outdoor Convenient Generator - Othman, Khairulnizam (Multidisciplinary Applied Research and Innovation, 2023)
In Malaysia, the problem of crop damage caused by pests often occurs, especially at night. Farmers often face this 'nightmare' because their crops are their source of finance. Because of that, farmers will find solutions to deal with this problem by doing various things. Hydro generators are equipment that can repel pests easily. Farmers will not suffer from damage to their crops due to the function of this generator. It is very user friendly and easy to carry anywhere. This generator requires a heavy current of water to generate electricity on the dynamo. Also, this generator is environmentally friendly as it only needs water for this generator to function. It can reduce the declining fuel consumption in Malaysia.